Properties of kenaf (Hibiscus cannabinus L.) paper impregnated with different formulations of synthetic wood pulp and polyacrylamide - Mohd Zawawi, Nurul Izzati (2013)
Kenaf fibre has been identified as an alternative fibre source due to its advantages in terms of physical and mechanical properties. It is found suitable to be utilized in the industry of pulp and paper making. The goals of the study are to produce water resistant paper by impregnation method and to determine its water resistant, physical and mechanical properties. Effects of polyacrylamide (PAM) addition to the water resistant paper produced are also determined. Important materials used throughout the study are kenaf whole stem, high and low branched of synthetic wood pulp (SWP); low and high molecular weight of PAM. The kenaf fibre was impregnated with SWP in order to create its water resistant character. In the first part of this study, kenaf fibre was impregnated with five different percentage of SWP at 10%,20%, 30%, 40% and 50%. The second part of this study was carried out to impregnate the SWPs with the addition of PAM as retention aid and dry strength agent. Water resistant, physical and mechanical test were carried out. The results showed that papers with water resistant property were successfully produced. The highest reading of water contact angle obtained was 84.3°. It is also found that a minimum of 20% SWP enough to meet the requirement for Cobb test as referred to Malaysian Standard. Higher amount of SWP was identified to reduce its mechanical properties especially the low branched SWP. Therefore, PAM was added to increase the strength of water resistant produced. Addition of PAM successfully increase water resistant property, however, PAM addition did not increase strength properties of water resistant paper produced. As conclusion, impregnation method is identified applicable to produce such water resistant paper from kenaf fibre provided that the amount and type of SWP are controlled.